Microbial processing of plant residues in the subsoil – The role of biopores. (October 2018) - Banfield, Callum C.; Pausch, Johanna; Kuzyakov, Yakov; Dippold, Michaela A.
Abstract: Most subsoil carbon (C) turnover occurs in biopore hotspots such as root channels and earthworm burrows. Biopores allocate large C amounts into the subsoil, where a vast capacity for long-term C sequestration is predicted. We hypothesise that organic matter (OM) cycling in biopores depends on their origin. Earthworm and root biopores were induced under field conditions and were sampled from the subsoil (45–75 and 75–105 cm) after two years of biopore formation. The effects of biopore formation on OM decomposition were studied by biomarkers: neutral sugars, cutin and suberin-derived lipids, lignin-derived phenols and free lipids. The degradation stage of OM was biopore type-specific but was only governed by the soil depth in root biopores. Degradation of OM increased from earthworm biopores to root biopores and bulk soil. Hemicelluloses (GM/AX ratio) were more strongly degraded than lignin side-chains (relative change from initial values). Two years of microbial processing during biopore formation increased the GM/AX ratio in earthworm biopores from 0.65 to 1.05 and in root biopores from 0.15 to 1.35 (both relative to source biomasses). Root biopores and bulk soil had the highest GM/AX ratios (1.2–1.3), hinting to rapid processing of plant residues and accumulation of microbial residues. The regular, frequent OM inputs by earthworms stimulated microbial growth and processing of mostly bioavailable OM and, thus, relatively enriched more persistent OM (e.g. lignin). Syringyl subunits of lignin underwent low (ratio changed from 0.35 to 0.55 relative to initial input) and vanillyl subunits underwent almost no processing in earthworm biopores indicating the preferential microbial utilisation of the easily available compounds frequently replenished by earthworm activity. After two years of decomposition of the root detritus, mainly structural plant material was enriched in root biopores. Short periods (6 months) of earthworm activity effectively recharged the highly processed OM in root biopores with fresh OM. In total, deep-rooting catch crops and short-term earthworm activities promote C accumulation in the subsoil followed by biopore-specific microbial processing predominantly governed by the C input frequency. As root biopores are up to 40 times more common than earthworm biopores, they dominate the OM input into subsoils. Such C inputs create several years lasting hotspots for preferential root growth and nutrient mobilisation in the subsoil. We conclude that root- and earthworm-derived biopores are vertical pathways for plant C from the soil surface into the subsoil and for intensive processing of litter C and sequestration of microbial necromass. Highlights: Subsoil C turnover in hotspots was evaluated using biomarkers as proxies. The hotspot type (earthworm vs root biopores) governs OM processing. Degree of OM processing highest in bulk subsoil, lower in biopores. Stronger processing of hemicelluloses than of lignin in biopores. Short-term anecic earthworm activities effectively renew biopore OM.